Economic Analysis of Health Care Utilization and Perceived Illness : Ethnicity and Other Factors - Paqueo, Vicente B.; Gonzalez, Christian Y. (World Bank, Washington, DC, 2014)
Paqueo and Gonzalez look at the determinants of health-seeking behavior of the Mexican population and within this context focus on the effect of ethnicity. They address the following questions: To what extent are the indigenous people at a disadvantage health care-wise and in what particular health services are they disadvantaged? Is the health care gap due to indigenous cultures by itself as opposed to the impact of socioeconomic differences? What policy instruments can be used to reduce the gap? The authors find that contrary to expectations, the indigenous people in Mexico tend to have a positive behavior toward modern preventive care compared with the nonindigenous population, holding socioeconomic factors constant. Apparently, there is no cultural barrier in regard to these services. But ethnicity remains negatively associated with the use of inpatient hospital care and medical and dental consultations. Insurance has a significant and positive effect on health care use. Therefore, it appears to be an effective instrument for addressing the health care disadvantages faced by the indigenous population in regard to inpatient care and the use of outpatient services of doctors, nurses, and dentists.